2020
DOI: 10.1128/iai.00034-20
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Mutagenesis Screen of Klebsiella pneumoniae Identifies Multiple Genes Important for Resisting Antimicrobial Activities of Neutrophils in Mice

Abstract: Klebsiella pneumoniae is a Gram-negative bacterial pathogen that causes a range of infections, including pneumonias, urinary tract infections, and septicemia, in otherwise healthy and immunocompromised patients. K. pneumoniae has become an increasing concern due to the rise and spread of antibiotic-resistant and hypervirulent strains. However, its virulence determinants remain understudied. To identify novel K. pneumoniae virulence factors needed to cause pneumonia, a high-throughput screen was performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 99 publications
0
30
0
Order By: Relevance
“…KPPR1S produces the enterobacterial common antigen (ECA) and LPS. A recent report showed that mutants in LPS and ECA pathways had reduced HMV (determined by sedimentation) ( 34 , 37 ). To more clearly ascertain if either of these exopolysaccharides contributed to HMV, we tested a strain with a disruption in wecA , which encodes an undecaprenyl phosphotransferase; this mutant produces normal levels of UA but lacks both LPS and ECA and is attenuated in the pneumonia model ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…KPPR1S produces the enterobacterial common antigen (ECA) and LPS. A recent report showed that mutants in LPS and ECA pathways had reduced HMV (determined by sedimentation) ( 34 , 37 ). To more clearly ascertain if either of these exopolysaccharides contributed to HMV, we tested a strain with a disruption in wecA , which encodes an undecaprenyl phosphotransferase; this mutant produces normal levels of UA but lacks both LPS and ECA and is attenuated in the pneumonia model ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even fuller datasets may be achieved by accessing the two other ordered K. pneumoniae transposon libraries, in addition to the one generated here. One such library contains 12,000 strains that correspond to 4,583 ORFs in strain KPN1H1 with the KPC-3 carbapenemase gene deleted and the other library has approximately 4,570 mapped transposon insertion site in ATCC 43816, although the number of unique ORFs disrupted is unclear [53, 54]. Altogether, these libraries represent invaluable genetic resources that will not only advance our understanding of K. pneumoniae pathogenesis and molecular biology within these specific strains, but can also be used as templates to generate insertional mutants in other strains or to study the contribution of individual domains to phenotypes of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are some important common factors among the requirements for infection of G. mellonella , and for an hv Kp murine lung infection (Paczosa et al . 2020 ). Genes contributing to both infection types include some of those encoding ubiquitous virulence factors such as capsule or siderophore importers.…”
Section: Resultsmentioning
confidence: 99%